2011
DOI: 10.1161/strokeaha.110.605477
|View full text |Cite
|
Sign up to set email alerts
|

Common Carotid End-Diastolic Velocity and Intima-Media Thickness Jointly Predict Ischemic Stroke in Taiwan

Abstract: Background and Purpose-In Asian populations, few studies investigated the association between stroke and common carotid artery intima-media thickness (IMT). Our previous case-control studies showed that low end-diastolic velocity (EDV) in common carotid artery, a potential hemodynamic marker of intracranial resistance, was associated with ischemic stroke. Therefore, we investigated the relationship between both EDV and IMT and incident ischemic stroke in an Asian population. Methods-Baseline data from 3175 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
(37 reference statements)
2
39
1
Order By: Relevance
“…Flow velocity, obtained by Doppler sonography, has been demonstrated to have prognostic value. 6 Low carotid flow enddiastolic velocity (EDV) is associated with an increased risk of stroke 6 and significantly increases the prediction of cardiovascular events. 7 The carotid flow pulsatility, calculated from the difference between peak systolic velocity (PSV) and EDV divided by the mean flow velocity, reflects the transmission of pulsatile energy into the cerebral microcirculation.…”
mentioning
confidence: 99%
“…Flow velocity, obtained by Doppler sonography, has been demonstrated to have prognostic value. 6 Low carotid flow enddiastolic velocity (EDV) is associated with an increased risk of stroke 6 and significantly increases the prediction of cardiovascular events. 7 The carotid flow pulsatility, calculated from the difference between peak systolic velocity (PSV) and EDV divided by the mean flow velocity, reflects the transmission of pulsatile energy into the cerebral microcirculation.…”
mentioning
confidence: 99%
“…Meanwhile, recent cross-sectional studies have reported that CIMT had a significant negative association with carotid artery flow velocity [11,12], and that CIMT was more highly associated with EDV than PSV in a large population [12]. However, another cross-sectional study reported that PSV is more associated with a cardiovascular event than EDV in hypertensive patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…3) CVD-related biochemical markers such as serum lipids, glucose, and C-reactive protein were not examined in this study. Demonstration of the association between CVD-associated biochemical markers and CIMT requires a crosssectional study of a larger population [11,39].…”
Section: Limitation Of the Studymentioning
confidence: 99%
See 2 more Smart Citations